2021
DOI: 10.18502/kss.v4i15.8230
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impact of COVID-19 Hoax on the Mental Health of Millennial Moms

Abstract: Hoaxes keep existing during this COVID-19 pandemic. They are indicated to be capable of heightening anxiety levels. Current works of literature about hoax-health impacts during the COVID-19 pandemic are still limited. Millennial, young generations, who are attached to the Internet technology, has the highest anxiety level. Millennial women or moms are already familiar with gadgets. They are surely exposed to hoaxes during this pandemic. Moms are the center of family defense. COVID-19 hoax … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…The reader's response can be in the form of panic or fear. This finding is related to the previous study conducted by Dharmastuti et al (2020) showing that any hoaxes during this pandemic can make people more anxious. One indication of health anxiety is experiencing panic and paranoia together with palpable physical symptoms.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The reader's response can be in the form of panic or fear. This finding is related to the previous study conducted by Dharmastuti et al (2020) showing that any hoaxes during this pandemic can make people more anxious. One indication of health anxiety is experiencing panic and paranoia together with palpable physical symptoms.…”
Section: Discussionsupporting
confidence: 87%
“…This point is in accordance with the findings of several previous studies conducted by Shiddiq (2020), Marbella et al (2021), andYunus &Rezki (2020), explaining that people who easily believe in hoax news have the potential to feel anxious, panicked, and afraid when reading it. Nevertheless, Dharmastuti et al (2020) proves that there is evidence that hoaxes might make people more anxious. There are still few current pieces of literature about the effects of hoaxes on human health during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the study found no link between the workplace environment and work-life conflicts. Interestingly, Dharmastuti et al (2020) revealed that COVID-19 hoaxes had the greatest impact on mothers' mental health due to health-institutional distrust and apparatus-government distrust. Due to the lack of cooperation in promoting the protocol, the COVID-19 pandemic prevention efforts were hampered.…”
Section: The Characteristics Of Millennialsmentioning
confidence: 99%
“…Due to the prominent roles millennial women play, greater effort should be placed in understanding the uniqueness of this particular group as a key factor in measuring progress towards gender equality. The literature on millennials' roles includes various disciplines, such as human resource management, business, marketing, social psychology, sociology, psychology, management, education, family studies, and women's studies (Rokis et al, 2018;Arham et al, 2019;Dharmastuti et al, 2020;Mohd Rosli et al, 2020;Habrich et al, 2021;Hanim & Naiemah, 2021;Lydia & Vighnarajah, 2021;Rozlana & Subramaniama, 2021;Suleman, 2021;Theopilus et al, 2021). For example, cultural influences shape the beliefs and values of a generation, which is significant to social acceptance and development.…”
Section: Roles Of Millennial Women In Malaysiamentioning
confidence: 99%
“…Regarded as the leading civil organizations focusing on anti-misinformation movement in the country, MAFINDO express its concern toward the infodemic caused by excessive misleading information that disrupt public health initiatives on mitigating the crises of COVID-19. Some studies proved that vaccine misinformations greatly impact on vaccine intentions (Dharmastuti et al, 2020;Jolley & Douglas, 2014).…”
Section: Introductionmentioning
confidence: 99%